MALES AND FEMALES SPEECH ACTS IN THE CLASSROOM SETTING - Nanda Marlina Abdul Samad; Sumarsih Sumarsih; Rahmad Husein (Universitas Negeri Medan, 2019)
This study investigates the speech acts that are realized by male and female lecturers in the classroom setting. The objectives of this study is to describe the kinds of speech acts are realized by male and female lecturers in the classroom. This research is conducted by using ethnographic design and qualitative approach. The data are the utterances of the lecturers at State Islamic Institute (IAIN) of Zawiyah Cot Kala Langsa. Islamic Education Department lecturers are chosen as the source of data. The data are obtained from observation and the transcription of the recorded of 4 lecturers of 2 males and 2 females lecturers during their teaching performance in the classroom. The findings show that there are three kinds of speech acts that are realized by males and females of 4 lecturers of 2 males and 2 females during their teaching performance in the classroom setting; They are locutionary acts, illocutionary acts and perlocutionary acts. In addition, from 5 types of illocutionary acts such as representatives, directives, commissive, expressive and declaratives, both males and females lecturers only implement 4 types of them; they are representatives, directives, commissive, and expressive, while declarative does not. In addition, in terms of the types of illocutionary acts, males lecturers mostly utilize representatives ways while females mostly implement both representatives and directives ways than other types during their teaching performance.KEYWORDS: Males and Females, Lecturer, Speech Acts, Classroom Setting